La Interpretación y el Desarrollo de los Parques Nacionales - Oltremari Arregui, Juan (Bosque (Valdivia), 1975)
Interpretation has become an important tool in national parks management, specially because of its contribution to the communication and learning of the different values involved in these natural areas. The present publication deals with the subject of interpretation, analizing its concept and its role in national parks development. It also includes a brief description of the current interpretive programs in chilean national parks, and the role that they play in the knowledge and understanding of the cultural and natural resources of the country.